2019
DOI: 10.1152/ajpheart.00482.2018
|View full text |Cite
|
Sign up to set email alerts
|

Mapping genetic modifiers of radiation-induced cardiotoxicity to rat chromosome 3

Abstract: Radiation therapy is used in ~50% of cancer patients to reduce the risk of recurrence and in some cases improve survival. Despite these benefits, doses can be limited by toxicity in multiple organs, including the heart. The underlying causes and biomarkers of radiation-induced cardiotoxicity are currently unknown, prompting the need for experimental models with inherent differences in sensitivity and resistance to the development of radiation-induced cardiotoxicity. We have identified the parental SS (Dahl sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(81 citation statements)
references
References 59 publications
3
78
0
Order By: Relevance
“…The repressor protein Keap1 binds and sequesters Nrf2, promoting Nrf2 ubiquitin-mediated degradation. The protein phosphoglycerate mutase family member-5 (PGAM5) is attached to the mitochondrial membrane and can form a complex with Keap1 and Nrf2 (37,61,62). Under oxidative conditions, Nrf2 is released from the complex, allowing nuclear accumulation of Nrf2 (60,62).…”
Section: Glutathione S-transferase Alpha 4 (Gsta4-4)/nrf2 Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The repressor protein Keap1 binds and sequesters Nrf2, promoting Nrf2 ubiquitin-mediated degradation. The protein phosphoglycerate mutase family member-5 (PGAM5) is attached to the mitochondrial membrane and can form a complex with Keap1 and Nrf2 (37,61,62). Under oxidative conditions, Nrf2 is released from the complex, allowing nuclear accumulation of Nrf2 (60,62).…”
Section: Glutathione S-transferase Alpha 4 (Gsta4-4)/nrf2 Pathwaymentioning
confidence: 99%
“…One week after 24 Gy of localized cardiac radiation, changes in expression of numerous gene pathways, including mitochondrial function, were seen between the sensitive and resistant rat hearts. Nrf2 was found to be an upstream regulator of many of the enriched pathways (61). Other preclinical investigations have studied the protective role of the Nrf2 pathway on radiation injury to cardiomyocytes and other cell lines, including embryonic fibroblasts and breast and lung epithelial cells (37).…”
Section: Glutathione S-transferase Alpha 4 (Gsta4-4)/nrf2 Pathwaymentioning
confidence: 99%
“…Moreover, some molecules may play roles in the process of RACVD, such as peroxisome proliferator-activated receptor gamma (PPAR-γ) (155), Growth differentiation factor 15 (GDF15) (153), and RhoA GTPase (125) that is essential to mediate the irradiation inhibition of endothelial cell migration. More recently, by using RNA-seq, differential gene-expression profiles have been identified in mice models, such as Nrf2, PDK1, and sirtuins (156). However, despite these lines of evidence, the whole picture of RACVD development is still not well-demarcated.…”
Section: Mir-146amentioning
confidence: 99%
“…Due to the increasing use of immune checkpoint inhibitors in cancer patients, as well as the variable state of adaptive immune cells in patients receiving chemotherapy and RT, it is important to better understand how adaptive immune cells alter the development and severity of RIHD. Using our previously published rat model of RIHD [26], we examined the role of T cells in cardiac radiation injury. We found that T-cell infiltration occurs in the heart after RT, and that localized heart irradiation leads to secretion of the T-cell-associated cytokines interleukin 2 (IL-2) and IL-13 [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…This zinc-finger nuclease approach was also performed on inbred Salt-Sensitive (SS) rats to create IL2RG −/− rats [33,34]. The immune-competent SS rat strain previously demonstrated increased sensitivity to localized cardiac RT compared to the Brown Norway (BN) strain [26]. Here, we report that SS IL2RG −/− rats also developed RIHD after localized high dose irradiation, with worse heart function measured via echocardiogram at three months post-RT compared to the SS immunocompetent (SS WT) rats.…”
Section: Introductionmentioning
confidence: 99%